Prevalence of contraceptive use among married women of reproductive age groups in a rural area of Bangladesh - Khan, Nirmeen Rifat; Jerifa, Sadia (Journal of Dhaka Medical College, 2015)
This was a descriptive cross-sectional type of study conducted with an aim to find out the prevalence of contraceptive use among married women of reproductive age group (15-49 years) in a rural area of Sreepur upazilla under Gazipur district. The study was conducted from February 2012 to June 2012. Out of 265 respondents, majority (27.17%) were found between the age group of 20-24 years where mean age was 28.12 years with SD of ±7.881 years. Among all the respondents 97.7% were Muslims. Maximum number of respondents (28.7%) were educated up to secondary school level but most of them (84.5%) were housewives. Majority (34%) of their husbands were service holders and businessmen each, 29.4% had monthly family income of 5,001-10,000/- Tk. This lower middle class comprised the highest group in our study. Among 265 respondents, 62.3% were using contraceptive methods at the time of study and rest 37.7% were not using due to some different reasons, such as pregnancy, breast feeding, eagerness to take child etc. Maximum couple (81.9%) took decision combindly to adopt contraceptive methods and most of them (69.8%) lived in a nuclear family. Majority (62.63%) had 1 to 2 children. Mostly used contraceptive method among ever users (81.69%) and current users (60%) was oral contraceptive pill. Majority (45.28%) mentioned no side effect from any of the methods. Relatives and neighbors were the highest informer (33.96%) than the family planning workers (20.75%) and even mass media (7.54%). In this study the prevalence of contraceptive use was found 62.3%. DOI: http://dx.doi.org/10.3329/jdmc.v23i1.22686 J Dhaka Medical College, Vol. 23, No.1, April, 2014, Page 7-13